Hypertension in India: Trends in wealth-related inequalities from the national family health surveys - Madhur Verma; Premkumar Ramasubramani; Shreyans Rai; Priyanka Sharma; Yuvaraj Krishnamoorthy; Rakesh Kakkar (Indian Journal of Public Health, 2023)
Introduction: India depicts a very high prevalence of hypertension. We need to learn more about the effect of wealth-related disparities on the prevalence of hypertension. The primary objective of this study was to assess temporal changes in the epidemiology of hypertension and associated wealth-related disparities among adults using two waves of nationally representative datasets from India. Methods: We did a secondary data analysis of the National Family Health Survey (NFHS) rounds 4 and 5. We included information from the two rounds from 699,686 and 108,791 males and 92,804 and 677,803 females. Weighted analysis and multivariate binomial regression were used to depict the prevalence and predictors of hypertension. Inequalities were estimated using the concentration index (CI) and concentration curves. Results: The weighted prevalence of hypertension among males increased from 14.6% to 16.7% among males, and from 8.8% to 9.9% among females, between NFHS-4 and NFHS-5. Prehypertension rose from 43.3% to 48.3% for males, and females, from 30.2% to 36.2% between the NFHS rounds. Overall, the CI among the males (0.078 and 0.050) and females (0.102 and 0.059) decreased from rounds 4 to 5, depicting a decrease in pro-poor wealth-related inequalities in hypertension prevalence in India. Conclusions: To conclude, the current analysis depicts that inequalities due to which hypertension was more prevalent in the wealthier classes in India are slowly disappearing. Therefore, we need to target the already exhausted poor patients with limited access to health-care resources to prevent them from further shifting beyond the line of poverty before these differences narrow down further.